1983
DOI: 10.1139/b83-094
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopy of embryo development in perennial and annual Medicago species

Abstract: The embryo of perennial Medicago sativa L. and annual M. scutellata (L.) Mill. have similar growth stages, but the perennial embryo is smaller and its rate of growth is slower than that of the annual by about 3 days. Transfer cells in the suspensor and embryo sac of late heart stages suggest different major pathways of nutrient flow in the two species. Transfusion tissue at the base of the embryo sac in the ovule of M. scutellata may facilitate solute transport and promote rapid embryo growth. Plastids in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
5
15
0
Order By: Relevance
“…This applies to S. reflexum as well. Such close contact between these organelles has also been observed in the suspensor cells of many species of, for example, Stellaria (Newcomb and Fowke, 1974), Phaseolus (Yeung and Clutter, 1978) and Medicago (Sangduen et al, 1983). The close contact between plastids and the nuclei and plasma membranes of plant cells suggests that this physical interaction may enhance the functional interactions between the organelles.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This applies to S. reflexum as well. Such close contact between these organelles has also been observed in the suspensor cells of many species of, for example, Stellaria (Newcomb and Fowke, 1974), Phaseolus (Yeung and Clutter, 1978) and Medicago (Sangduen et al, 1983). The close contact between plastids and the nuclei and plasma membranes of plant cells suggests that this physical interaction may enhance the functional interactions between the organelles.…”
Section: Discussionmentioning
confidence: 71%
“…The abundance of mitochondria adjacent to the ingrowths suggests high energy requirements for absorption and movement of nutrients across the cell membrane by the cells in question. The occurrence of such mitochondria has been found in the suspensor cells of many species: Phaseolus coccineus (Yeung and Clutter, 1978), Capsella bursapastoris (Schulz and Jensen, 1969), Pisum sativum (Marinos, 1970a), Stellaria media (Newcomb and Fowke, 1974), Tropaeolum majus (Nagl, 1976), Medicago (Sangduen et al, 1983), Alisma plantago-aquatica and A. lanceolatum (Bohdanowicz, 1987), Paphiopedilum delenatii (Lee et al, 2006), Sempervivum arachnoideum and Jovibarba sobolifera (Kozieradzka-Kiszkurno et al, 2011b). Wall ingrowths similar to those in S. reflexum have also been observed in two Sedum species: S. acre and S. hispanicum (Kozieradzka-Kiszkurno and Bohdanowicz, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, acellulosic wall structure appears in the endospermic cytoplasm; Marinos suggested that this might be involved in the precise positioning of the embryo within the embryo sac and in the control of nutrient transfer to the embryo. Similarly, in sunflower (Newcomb and Steeves, 1971), cotton (Schulz and Jensen, 1977), and alfalfa (Sangduen et al, 1983), the inner wall of the embryo sac produces wall invaginations, which appear to be specialized transfer structures, into the endosperm.…”
Section: Relationships Between Endosperm Embryo and Maternal Tissuesmentioning
confidence: 99%
“…One is expressed not only in seeds but also in leaves, stems, and roots. The presence of PEPC protein and/or mRNA has also been reported in germinating Sorghum bicolor seeds [20], in developing seeds of Vicia faba [8], Vitis vifera [13], castor bean [6], Oryza sativa [38], and in developing and germinating wheat grains [16].…”
Section: Introductionmentioning
confidence: 87%